Theory of planned behavior, self-stigma, and perceived barriers explains the behavior of seeking mental health services for people at risk of affective disorders - Maryam Damghanian; Mehran Alijanzadeh (Wolters Kluwer Medknow Publications, 2018)
Introduction: To use the theory of planned behavior (TPB) incorporated with self-stigma and perceived barriers to investigate the nature of help-seeking behaviors in a community sample at risk of anxiety or depression in Iran. Methods: Participants at risk of anxiety or depression screened by Hospital Anxiety and Depression Scale (n = 1011) completed the following questionnaires at baseline: Factors in TPB, Self-Stigma in Seeking Help Scale, and perceived barriers in seeking help. Two years later, their help-seeking behavior (i.e., visiting a specialist) was retrieved from their medical records. Models using TPB concepts and incorporated with self-stigma and perceived barriers were tested by structural equation modeling. Results: The effects of TPB concepts, self-stigma and perceived barriers on help-seeking behaviors (i.e., visiting a specialist for mental health problems) were supported by the excellent data-model fit indices: Comparative fit index = 0.997; Tucker-Lewis index = 0.965; root mean square of error approximation (RMSEA) = 0.028; and weighted RMSEA = 0.386. All the path coefficients were significant, except for the path between perceived barriers and help-seeking behavior. Perceived behavioral control had the strongest coefficient (standardized coefficient = 0.547); subjective norm had the weakest coefficient (standardized coefficient = 0.061). In addition, perceived barriers were indirectly associated with help-seeking behaviors. Conclusion: TPB is an effective model to explain the help-seeking behaviors for people at risk of anxiety or depression. In addition, self-stigma and perceived barriers may be simultaneously considered when clinicians want to prevent an individual with depression or anxiety from not seeking proper help on their mental health problems.